2020
DOI: 10.3390/coatings10100959
|View full text |Cite
|
Sign up to set email alerts
|

Application of Infrared Spectroscopy in Prediction of Asphalt Aging Time History and Fatigue Life

Abstract: Based on attenuated total reflection Fourier-transform infrared (ATR-FTIR) spectroscopy and principal component analysis (PCA), four kinds of asphalt (two kinds of matrix asphalts, TPC70# and JL70# and two kinds of modified asphalts, SBS-1 and SBS-2) were aged using the rolling thin-film oven test (RTFOT). The multiple stress repeated creep recovery test (MSCR) was carried out on an AR1500ex dynamic shear rheometer (DSR). The PCA was carried out on the attenuated total reflection infrared spectrum of a pretrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The infrared spectrum of tranexamic acid (red line) in Figure 2 provides an absorption response similar to that in the literature, both in terms of spectrum and specific wave numbers [25]. Tranexamic acid was quantified using three primary peaks in the fingerprint area with wavenumbers ranging from 1800 to 650 cm −1 , notably wave numbers 1638.2, 1541.3, and 1384.7 cm −1 [26][27][28].…”
Section: Preliminary Study Of Infrared Spectrophotometrymentioning
confidence: 62%
“…The infrared spectrum of tranexamic acid (red line) in Figure 2 provides an absorption response similar to that in the literature, both in terms of spectrum and specific wave numbers [25]. Tranexamic acid was quantified using three primary peaks in the fingerprint area with wavenumbers ranging from 1800 to 650 cm −1 , notably wave numbers 1638.2, 1541.3, and 1384.7 cm −1 [26][27][28].…”
Section: Preliminary Study Of Infrared Spectrophotometrymentioning
confidence: 62%
“…Then, the softening point slightly decreased for 3.6% for 1%, 3.96% for 2%, 5.05% for 3%, 6.49% for 4% and 7.03% for 5% POMS. This result showed that POMS caused the dilution effect like bio-oil [10,15,16]. Xin et al, [16] suggest that bio-oil needs to be selected carefully to ensure the asphalt binder achieves the appropriate characteristic.…”
Section: Penetration and Softening Pointmentioning
confidence: 99%
“…The samples are then promptly introduced into the RTFO, which has been preheated to 163℃ and then rotated at 15 revolutions per minute. At the same time, 4000 mL/minute of hot air was continuously blasted in [10].…”
Section: Preparation Of Modified Asphalt Bindermentioning
confidence: 99%
“…Fatigue cracking is one of the most frequent types of failure in asphalt mixtures [1]. This phenomenon is related to the deterioration experienced by pavements because of the repeated application of loads with less magnitude than the maximum resistance of the materials forming them [2].…”
Section: Introductionmentioning
confidence: 99%